2019
DOI: 10.3847/1538-4357/ab158d
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Emission Mechanism and Magnetic Field of Neutrino Blazars with Multiwavelength Polarization Signatures

Abstract: The characteristic two-component blazar spectral energy distribution (SED) can be of either leptonic and/or hadronic origins. The potential association of the high-energy neutrino event IceCube-170922A with the flaring blazar TXS 0506+056 indicates that hadronic processes may operate in a blazar jet. Despite multi-wavelength follow-ups of the event and extensive theoretical modelings, the radiation mechanisms and the underlying magnetic field strength and configuration remain poorly understood. In this paper, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…This is done through a Compton scattering module that works similarly as the 3DPol code, but without the polarization dependence. This is because the PD due to SSC and EC is generally very low in the blazar emission region, which is unlikely to be observed (Bonometto et al 1970;Paliya et al 2018;Zhang et al 2019;Dreyer & Böttcher 2021). To summarize, we consider two seed photon fields for the Compton scattering in the radiation transfer simulation: an inhomogeneous and fast-evolving synchrotron photon field for the SSC, and a uniform and stationary black body photon field for the EC.…”
Section: Radiation Transfer Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…This is done through a Compton scattering module that works similarly as the 3DPol code, but without the polarization dependence. This is because the PD due to SSC and EC is generally very low in the blazar emission region, which is unlikely to be observed (Bonometto et al 1970;Paliya et al 2018;Zhang et al 2019;Dreyer & Böttcher 2021). To summarize, we consider two seed photon fields for the Compton scattering in the radiation transfer simulation: an inhomogeneous and fast-evolving synchrotron photon field for the SSC, and a uniform and stationary black body photon field for the EC.…”
Section: Radiation Transfer Setupmentioning
confidence: 99%
“…As a result, in the high state the 0.1 GeV γ-ray band shows a rather flat spectrum dominated by the SSC contribution, but in the low state it exhibits a rising spectrum dominated by the EC contribution (see Figure 2). This issue generally applies to any blazar spectral modeling with multiple radiation processes in the highenergy spectral component, including the lepto-hadronic models (Böttcher et al 2013;Cerruti et al 2019;Zhang et al 2019;Keivani et al 2018), which can be tested with future MeV γ-ray telescopes such as AMEGO (McEnery et al 2019;Rani et al 2019b). We note that our setup targets at a flat-spectrum radio quasar that peaks in the GeV band, and the harder-when-brighter trend is clear around or beyond the peak.…”
Section: Implications For Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the optical and high-energy emissions are likely from the same emission region, they should share the same magnetic field morphology. In this situation, [52,107] have shown that the high-energy polarization degree may be detectable with high-energy polarimeters, which can distinguish the leptonic and hadronic models (see Figure 9 left). [109] has studied the temporal behavior of multi-wavelength polarization signatures.…”
Section: Multi-wavelength Polarimetrymentioning
confidence: 98%
“…However, the very dynamical and complex nature of AGN jets prevents the use of simple analytical models. Recent first-principle numerical simulations have attempted to consistently combine plasma dynamics and radiation processes to directly compare with observations [88,98,104,105,107], which have shown interesting predictions in polarization variability. With the development of CPU and GPU computing in the next decade, this multi-physics approach will revolutionize our understanding of jet dynamics.…”
Section: Polarization Variabilitymentioning
confidence: 99%